2017
DOI: 10.1111/ijn.12574
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of applying flipped learning to clinical nursing practicums for nursing students in Korea: A randomized controlled trial

Abstract: The findings indicate that applying flipped learning allows students to conduct individualized learning with a diversity of clinical cases at their own level of understanding and at their own pace before they participate in real-world practicums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Learner motivation affected learner satisfaction in both the FMCM and FMPM groups, which is in agreement with the findings of Kim et al (). Hawks () and McLaughlin et al () considered it important to provide detailed evidence and motivation in order to promote student participation in flipped learning, and the present result also supports learning satisfaction being higher in students with higher intrinsic motivation who perform the activities for their own satisfaction with learning activities (Han, ) and that high motivation facilitates learning and increases attention and academic achievement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Learner motivation affected learner satisfaction in both the FMCM and FMPM groups, which is in agreement with the findings of Kim et al (). Hawks () and McLaughlin et al () considered it important to provide detailed evidence and motivation in order to promote student participation in flipped learning, and the present result also supports learning satisfaction being higher in students with higher intrinsic motivation who perform the activities for their own satisfaction with learning activities (Han, ) and that high motivation facilitates learning and increases attention and academic achievement.…”
Section: Discussionsupporting
confidence: 92%
“…The required number of participants was calculated using G*Power (version 3.1.7) (Faul, Erdfelder, Buchner, & Lang, 2009). For an effect size ( f 2 ) of 0.31, significance level (α) of 0.05, power (1 − β) of 0.9, and the eight predictive variables used in a previous study (Kim et al, 2017), the calculated sample size was 70 participants, and so 82 participants were required based on a predicted dropout rate of 15%.…”
Section: Research Design and Participantsmentioning
confidence: 99%
“…There is ample evidence that an active e-learning approach is positively associated with cognitive skills, including critical thinking [ 15 16 17 ]. Several recent experimental studies in nursing have suggested that content knowledge and cognitive skills [ 18 ], student confidence in performing core nursing skills [ 19 ], student satisfaction and achievement [ 20 21 ], and other learning outcomes [ 8 ] improved after participation in flipped learning nursing courses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the FL model involves a deeper integration of the pre-and in-class components in which the main concepts align with the knowledge that is imparted. As a result, students develop at their own pace while adopting self-directed learning, and active interaction occurs between students and professors (Kim, Kim, Cho, & Jang, 2017). FL is also considered to be an extension of the flipped classroom, which includes a more active and collaborative environment (O'Connor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%